2019
DOI: 10.29036/jots.v10i19.115
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the Selected Business Environment Aspects by Service Firms

Abstract: The business environment is a profound concern for the state and institutions to make it encouraging to boost entrepreneurship. Given such relevance of the business environment, this paper aims to link selected business environment aspects to business sector. The study identified the perceived differences between sectors in the Czech and Slovak Republics and then a comparison of a similar group of firms. To shape the study, survey-based research planned and conducted in two segments of firm’s (service and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…Firms operating in Slovakia are more social responsible than those in the Czech Republic. This finding is in line with prior studies which identified some differences between the two countries in terms of business environment Khan et al, 2019;Koisova et al, 2018), or having substantial interest in entrepreneurship (Çera et al, 2018;Dvorský et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Firms operating in Slovakia are more social responsible than those in the Czech Republic. This finding is in line with prior studies which identified some differences between the two countries in terms of business environment Khan et al, 2019;Koisova et al, 2018), or having substantial interest in entrepreneurship (Çera et al, 2018;Dvorský et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…It is logical, although financial risk was significant in the pre-crisis era as well (e.g. the case study from Ajaz Khan et al (2019) in the SR and CR service firms, Štefko et al (2020) in the Slovak Spa Industry etc.). During a crisis, the finances take the biggest toll, given the reduction of production and sales, disruption of supply chains, change in demand structures as well as employment processes.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…However, in the current scenario, businesses operate in a very complex and fluctuating environment. The business environment is a profound concern for the state and institutions to make it encouraging to boost entrepreneurship (Ajaz Khan et al, 2019). This brings different types of risk exposure internally as well as externally, and makes SME operations very challenging.…”
Section: Introductionmentioning
confidence: 99%